Peripheral Blood Derived Cell Trafficking for Cardiac Regeneration - Post, Simone; Goumans, Marie-Jose; A. Doevendans, Pieter (Current Stem Cell Research & Therapy, 2010)
Systemic available circulating cells play a role in cardiac maintenance and ameliorate cardiac recovery and repair after myocardial infarction. However, only a small number of cells will be incorporated during cardiac damage. Cell mobilization, homing to the ischemic myocardium and engraftment are complex processes depending on many adhesion molecules, proteases, chemokines and their receptors. Physiologic and pathophysiologic circumstances, cytokines, chemokines and certain drugs are able to influence these processes. For cardiovascular regeneration, understanding how mobilization and homing of blood derived cells is regulated and can be modulated as well as identification of cell populations able to regenerate the heart or reduce damage after myocardial infarction is essential for the development of successful cell based therapies.
Keywords: cardiac function